Myeloid cell MHC I expression drives CD8+ T cell activation in nonalcoholic steatohepatitis - Adams, Victoria R.; Collins, Leonard B.; Williams, Taufika Islam; Holmes, Jennifer; Hess, Paul; Atkins, Hannah M.; Scheidemantle, Grace; Liu, Xiaojing; Lodge, Mareca; Johnson, Aaron J.; Kennedy, Arion (Frontiers in Immunology, 2024)
Background & Aims: Activated CD8 + T cells are elevated in Nonalcoholic steatohepatitis (NASH) and are important for driving fibrosis and inflammation. Despite this, mechanisms of CD8 + T cell activation in NASH are largely limited. Specific CD8 + T cell subsets may become activated through metabolic signals or cytokines. However, studies in NASH have not evaluated the impact of antigen presentation or the involvement of specific antigens. Therefore, we determined if activated CD8 + T cells are dependent on MHC class I expression in NASH to regulate fibrosis and inflammation.We used H2Kb and H2Db deficient (MHC I KO), Kb transgenic mice, and myeloid cell Kb deficient mice (LysM Kb KO) to investigate how MHC class I impacts CD8 + T cell function and NASH. Flow cytometry, gene expression, and histology were used to examine hepatic inflammation and fibrosis. The hepatic class I immunopeptidome was evaluated by mass spectrometry.In NASH, MHC class I isoform H2Kb was upregulated in myeloid cells. MHC I KO demonstrated protective effects against NASH-induced inflammation and fibrosis. Kb mice exhibited increased fibrosis in the absence of H2Db while LysM Kb KO mice showed protection against fibrosis but not inflammation. H2Kb restricted peptides identified a unique NASH peptide Ncf2 capable of CD8 + T cell activation in vitro. The Ncf2 peptide was not detected during fibrosis resolution.Conclusions: These results suggest that activated hepatic CD8 + T cells are dependent on myeloid cell MHC class I expression in diet induced NASH to promote inflammation and fibrosis. Additionally, our studies suggest a role of NADPH oxidase in the production of Ncf2 peptide generation.